Variability of Acetabular Coverage Between Supine and Weightbearing Pelvic Radiographs. (November 2014) - Pullen, W. Michael; Henebry, Andrew; Gaskill, Trevor
Background: Radiographic measures of acetabular coverage are essential screening tools used to characterize bony structure contributing to femoroacetabular impingement (FAI). Small changes in pelvic tilt result in altered radiographic measures of acetabular coverage. Positional changes in pelvic tilt are known to occur between the supine and weightbearing positions. It is unclear whether alteration of pelvic tilt between these positions is clinically sufficient to influence measures of acetabular coverage. Purpose/Hypothesis: To determine whether, and to what degree, imaging position (supine vs weightbearing) is capable of altering several measures of acetabular orientation: pubic symphysis to sacrococcygeal distance (PSSC), angle of Sharp (SA), Tönnis angle (TA), percentage of acetabular crossover (CO), and lateral center-edge angle of Wiberg (LCEA). The hypothesis was that imaging position would significantly alter all measures of acetabular orientation. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: A total of 50 consecutive symptomatic hips referred to a single provider for FAI were evaluated with standardized supine and weightbearing anteroposterior pelvic radiographs. Two independent reviewers blinded to patient positioning reviewed each radiograph at 2 separate time points. Mean measurements in each position were compared by use of paired Student t tests, and a Bonferroni-adjusted significance level of P = .01 was used to represent significance. Results: Statistically significant differences between the supine and weightbearing radiographs were identified for PSSC and all measures of acetabular coverage ( P < .003). The mean PSSC decreased between the supine and weightbearing positions by an average of 13.4 mm ( P < .001), thereby resulting in decreased mean LCEA, TA, SA, and CO of 1.2°, 1.3°, 0.8°, and 6.3%, respectively ( P < .002). The change in positional pelvic tilt was not uniformly predictable and accounted for large measurement changes in some individuals. PSSC also demonstrated considerable inter- and intrasubject variability but averaged 55.8 mm supine and 44.9 mm weightbearing for females and 37.0 mm supine and 20.6 mm weightbearing for males. Conclusion: In this study of nonarthritic adult patients with hip pain, the data indicate that positional changes are capable of significantly altering pelvic tilt and radiographic measures of acetabular coverage. It appears that the weightbearing position typically, but not universally, correlates with additional posterior pelvic tilt and decreased measures of acetabular coverage. Individual positional variability can contribute to large-magnitude changes in radiographic acetabular measures.